Possibilities of Development of Informatics Thinking of Pupils and Students Using the Model of Subject-Didactic Competences of Teachers - KLEMENT, MILAN; BRYNDOVÁ, LUCIE (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
The development and incorporation of the concept of the development of computational thinking into the curriculum of computing subjects is currently one of the major challenges facing the Czech school system. However, such a concept of teaching presupposes a targeted development of content-subject and didactic- pedagogical competencies of teachers necessary for the development of computational thinking in their pupils and students. Thus, the present paper deals with the possibility of defining a general model of subject-matter and didactic competences of teachers supporting the development of computational thinking in pupils and students.